2020
DOI: 10.1016/j.ajp.2020.102077
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress, behavioural symptoms and mood states among school-age children with attention-deficit/hyperactive disorder during the COVID-19 outbreak

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
313
7
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(360 citation statements)
references
References 8 publications
17
313
7
23
Order By: Relevance
“…It is plausible that the worsened inattentive symptoms in our patients were associated with psychological trauma due to being quarantined. A very recent study 6 showed that ADHD symptoms in children signi cantly worsened in comparison to the baseline state during the COVID-19 outbreak in China and that children's negative mood state was associated with ADHD symptoms. It was also reported 7,8 that children who were isolated or quarantined during pandemic diseases were more likely to develop acute stress disorder, adjustment disorder, and grief.…”
Section: Main Textmentioning
confidence: 99%
“…It is plausible that the worsened inattentive symptoms in our patients were associated with psychological trauma due to being quarantined. A very recent study 6 showed that ADHD symptoms in children signi cantly worsened in comparison to the baseline state during the COVID-19 outbreak in China and that children's negative mood state was associated with ADHD symptoms. It was also reported 7,8 that children who were isolated or quarantined during pandemic diseases were more likely to develop acute stress disorder, adjustment disorder, and grief.…”
Section: Main Textmentioning
confidence: 99%
“…In samples of children with previous mental illnesses in other countries, their conditions have been reported to be negatively affected by the pandemic [ 6 ]. This is the case of children with attention-deficit/hyperactivity disorder [ 7 ] and autism [ 8 ]. The variables that were more predictive of already existing conditions worsening were children’s and parents’ general worse mood, less time dedicated to studying [ 7 ], and not receiving support from the school [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of children with attention-deficit/hyperactivity disorder [ 7 ] and autism [ 8 ]. The variables that were more predictive of already existing conditions worsening were children’s and parents’ general worse mood, less time dedicated to studying [ 7 ], and not receiving support from the school [ 8 ]. Older age and living with a single parent were protection factors against more intense behavior problems in autistic children [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children with neuropsychological developmental disorders are more sensitive to disease-related information and are more likely to display behavioral problems. 26,27 Guideline-recommended strategies for those with pre-existing mental illness, such as ADHD and ASD, are therefore needed to be reinforced to manage children's disruptive behaviors. 45 Since national social distancing measures present considerably increased challenges to children with a mental illness history, mental training programs that help healthcare professionals deliver timely psychotherapy to children in poor mental health conditions should be implemented in the face of COVID-19 crisis.…”
Section: Discussionmentioning
confidence: 99%
“…25 Children who had a history of somatic symptom disorder (SSD), autism spectrum disorder (ASD), and attention de cit hyperactivity disorder (ADHD) were also reported to experience an exacerbation of psychological symptoms. [26][27][28] Emotional needs…”
Section: Psychological Impactmentioning
confidence: 99%